Virtual Exchange: A Comparative View of Teaching and Learning in Elementary Education - Renner, Günter (Internationalization of Teacher Education in Higher Education: Theories, Concepts and Practical Approaches of Virtual, Blended and Physical Mobility, 2024)
This article gives an insight into the virtual exchange course "A Comparative View of Teaching and Learning in Elementary Education", in which students from Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU) in Germany and students from the University of Latvia worked together on a range of topics over a period of 12weeks in 2021and 2022. The course provides participants with a comparative overview of elementary education in two countries; alongside experiencing the other country's education system, participants investigate fundamental aspects of teaching, learning, and assessment at its elementary schools. Students tackle tasks together online in small groups, usually comprising six students (three from Germany and three from the other country), and engage in discussion, sharing views specific to their own national backgrounds. The course was selected by the Innovation in Learning Institute at FAU as an example of good practice in online teaching and nominated, in the context of the EU funded FRAMES project, as a positive scenario relating to the adoption and accreditation of virtual exchange programs in higher education across Europe. It recently received an award for excellence in teaching from FAU's Department of Education.<br
Keywords: Virtual Exchange; Primary Education